2017
DOI: 10.14257/ijsia.2017.11.5.02
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Model for Exploring the Factors Influencing Information Security Culture

Abstract: Human behavior is considered as one of the main threats in an organization. Owing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Tang et al (2016), Van Niekerk and Von Solms (2010) and Solomon and Brown (2020) investigated the relationship between information security culture and organizational culture, Alnatheer (2014), Shkarlet et al (2020) and Sas et al (2020) explored assessment and measurement of information security culture, while other researchers focus their work on determining dimensions (factors) of information security culture (Sherif and Furnell, 2015; Nel and Drevin, 2019; Arbanas, 2020). On the other hand, Van Niekerk and Von Solms (2010) and Mahfuth et al (2017a, b) worked on development of conceptual models and revealed that there is a positive relationship between levels of knowledge and employees' behaviour, which is not surprising since Bouhnik et al (2021) have shown that, in order for the security behaviour to become their second nature, people must first be educated to do so.…”
Section: Theoretical Background and Motivationmentioning
confidence: 99%
See 4 more Smart Citations
“…Tang et al (2016), Van Niekerk and Von Solms (2010) and Solomon and Brown (2020) investigated the relationship between information security culture and organizational culture, Alnatheer (2014), Shkarlet et al (2020) and Sas et al (2020) explored assessment and measurement of information security culture, while other researchers focus their work on determining dimensions (factors) of information security culture (Sherif and Furnell, 2015; Nel and Drevin, 2019; Arbanas, 2020). On the other hand, Van Niekerk and Von Solms (2010) and Mahfuth et al (2017a, b) worked on development of conceptual models and revealed that there is a positive relationship between levels of knowledge and employees' behaviour, which is not surprising since Bouhnik et al (2021) have shown that, in order for the security behaviour to become their second nature, people must first be educated to do so.…”
Section: Theoretical Background and Motivationmentioning
confidence: 99%
“…Also, there were a number of systematic literature reviews related to information security culture (Alhogail and Mirza, 2014; Alnatheer, 2014; Karlsson et al , 2015; Hassan et al , 2015; da Veiga et al , 2020) with the conclusion that existing research is largely theoretical or descriptive, and there is a lack of knowledge in identifying factors and measuring the impact on information security culture. Many researchers pointed out that there is a growing need for comprehensive empirical research in this area (Mahfuth et al , 2017a, b; Alhogail and Mirza, 2014; Karlsson et al , 2015), which was one of the motives for this research.…”
Section: Theoretical Background and Motivationmentioning
confidence: 99%
See 3 more Smart Citations